Biochemical studies on bovine adenovirus type 3. II. Incomplete virus. - Igarashi, K (1975)
Incomplete virus of oncogenic bovine adenovirus type 3 (BAV3) was highly purified and its biological activity was studied. The production of incomplete virus was found to increase with a high multiplicity of infection and with a large amount of arginine in the growth medium. On infection of contact-inhibited mouse cells, incomplete virus induced cellular DNA synthesis and focus formation. Moreover, this virus was oncogenic to newborn hamsters. On infection of calf kidney cells, a permissive cell line, viral early and late RNA, viral DNA, and almost all the viral late proteins were produced, but no mature progeny virus was detected. It is, therefore, suggested that incomplete virus of BAV3 may be unable to synthesize a protein(s) (perhaps a kind of maturation protein[s]) essential for assembly of viral macromolecules for maturation.